64.3: Development of 55‐inch UHD AMOLED TV. Issue 1 (June 2015) - Wu, Zhongyuan; Yuan, Guangcai; Xie, Hongjun; Cao, Kun; Li, Yongqian; Zeng, Siheng; Zhou, Yang; Yang, Fei; Cheng, Jun; Shi, Huaiting; Ye, Lankai; Yu, Jianwei; et al.
Abstract : In this paper, we present a 55" UHD AMOLED TV developed at G8.5 using IGZO backplane and tandem white‐OLED with COA (color filter on array), which is considered as one of the feasible options for mass production. We also implement the external optical compensation to achieve good display uniformity.